Another Acknowledgement on the American Strategy on the War in Iraq - Mohamed, Raghad Raeed (Journal of Economic Development, Environment and People, 2019)
The main objective of this article is to describe and evaluate some of the central elements of the US strategy in Iraq, from the beginning of the war to the present. In this case, the term "strategy" refers mainly to the political-military actions directly related to the wider context of the war on terrorism. But the American strategy also involves secondary concerns: those that force the US, as a world power, to have constant commitments and implications in the evolution of the international system. As a result, the US strategy is not just about how the US manages military, anti-terrorist, regional stabilization and nation-building operations in Iraq, but also about how Washington defines its priorities, its political and military actions, and allocates resources not just to achieve the central objectives, but also to solve various side problems of the international scene. When talking about the current situation in Iraq, the starting point of the discussion must be the legitimacy of the US military intervention in 2003. From a strictly legal perspective, as from a strictly moral perspective, the US intervention in Iraq seems not to be legitimate enough. In order to establish a theoretical basis for the US intervention in Iraq, we must analyze the situation through the perspective of realism, as a theory of international relations, and we must recall some of Morgenthau's basic ideas.